The effect of corporate social responsibility disclosure in good corporate governance relations on financial performance - MEYSIN; KARTINI HANAFI IDRIS; DARWIS SAID (International Journal of Multidisciplinary Research and Studies, 2023)
This study aims to analyze the influence of corporate social responsibility (CSR) in the relationship of good corporate governance (managerial ownership, institutional ownership, foreign ownership, independent commissioners and audit committees) on financial performance. This research was conducted in the coal sub-sector companies. By using quantitative research methods. The population in this study were all companies in the coal sub-sector consisting of 31 companies. The sample was determined using a purposive sampling technique which obtained 11 companies as samples in the study. The theories used in this research are agency theory, signaling theory, and attribution theory. This study uses secondary data, namely data obtained from the official website of the Indonesia Stock Exchange (IDX) and the official website of each company. The research data were analyzed using Moderation Regression Analysis (MRA) using SPSS software. The results showed that partially managerial ownership, independent commissioners and committees did not significantly influence financial performance. However, institutional ownership and foreign ownership have a significant effect on financial performance. CSR disclosure moderates the effect of managerial ownership, institutional ownership, foreign ownership, and audit committees on financial performance partially, but CSR disclosure does not moderate the effect of independent commissioners on financial performance.